1990
DOI: 10.1115/1.2909405
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Study of Turbulent Flows in a Channel With Two Pairs of Turbulence Promoters in Tandem

Abstract: Measurements and computations are presented of mean velocity and turbulence intensity for an arrangement of two pairs of turbulence promoters mounted in tandem in developing channel flow. The Reynolds number (ReD) and the pitch ratio (PR) were varied in the range of 1.2 × 104 to 1.2 × 105 and 1 to 100, respectively. The three pitch ratios 5, 10, 15 were found to provide three characteristic flows which are a useful test of the computational models. The effects of PR on the reattachment lengths and the pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(16 citation statements)
references
References 0 publications
2
12
0
2
Order By: Relevance
“…However at every location in the channel, the 0 / Nu Nu values decrease as Re increases. Liou et al [21] and Liou et al [22] showed a similar trend. Note that due to the evolution of the Dittus-Boelter Nusselt number, increasing with Re number, Nu values increase with the Reynolds number.…”
Section: Nu Nu =supporting
confidence: 63%
“…However at every location in the channel, the 0 / Nu Nu values decrease as Re increases. Liou et al [21] and Liou et al [22] showed a similar trend. Note that due to the evolution of the Dittus-Boelter Nusselt number, increasing with Re number, Nu values increase with the Reynolds number.…”
Section: Nu Nu =supporting
confidence: 63%
“…The structures generated in this manner had length scales proportional to the roughness height "k" and were found to blend into the outer flow farther away from the roughness. Subsequent flow visualization studies of individual grooves by Liou et al (1990) and Djenidi et al (1994) provide additional evidence supporting these observations. The rough-wall study of Grass (1971) in a free-surface channel flow using hydrogen bubbles clearly identified the differences of near-wall ejection and inrush (sweep) events between smooth and rough walls (sand and rounded pebbles).…”
Section: Roughness Effects In the Near-wall Regionsupporting
confidence: 50%
“…It is postulated that signi"cant interaction between the two obstacles can exist only if the #ow reaching the downstream one has not recovered fully its equilibrium condition. For the case of developed turbulent #ow, the typical length of the separated region behind a very thin obstacle is 8}12 times its height h, while recovery may well require an additional length of 10}15h (Bullock et al 1990;Scho"eld & Logan 1990;Liou et al 1990). These lengths can be compared to the experimental bounds obtained for l R /h and l K /h and shown in Table 1.…”
Section: A Model For the Behaviour Of The Systemmentioning
confidence: 98%